2007
DOI: 10.1111/j.1467-9760.2007.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Debate: Evading the Paradox of Universal Self‐Ownership*

Abstract: A paradox troubles the foundations of libertarian political thought. This paradox is the paradox of universal self-ownership and it arises from the interaction of two of the primary claims of libertarian political philosophers:(1) that all individuals are (at least originally) self-owners, 1 and (2) that all individuals own the products of their labour. Libertarians hold that these two claims are consistent with each other, and indeed that (2) can be derived from (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…In other words, you first need to try to extract "concerns involving the self" from regret, worry and an-Psychology than ownership for real happiness. Recent philosophical studies have suggested that further research is needed to bring into sharper focus the distinction between self-ownership and lack of ownership (i.e., of one's own body), both philosophically and psychologically (Pendlebury et al, 2001;Uyl & Rasmussen, 2003;Taylor, 2005;Curchin, 2007;Ypi, 2011). In terms of the present research, does the condition of "Being unable to detach from concerns involving the self" mean that one philosophically and/or psychologically owns "concerns involving the self" in one's "Omoi"?…”
Section: Future Directionsmentioning
confidence: 99%
“…In other words, you first need to try to extract "concerns involving the self" from regret, worry and an-Psychology than ownership for real happiness. Recent philosophical studies have suggested that further research is needed to bring into sharper focus the distinction between self-ownership and lack of ownership (i.e., of one's own body), both philosophically and psychologically (Pendlebury et al, 2001;Uyl & Rasmussen, 2003;Taylor, 2005;Curchin, 2007;Ypi, 2011). In terms of the present research, does the condition of "Being unable to detach from concerns involving the self" mean that one philosophically and/or psychologically owns "concerns involving the self" in one's "Omoi"?…”
Section: Future Directionsmentioning
confidence: 99%
“…From a philosophical perspective, one respondent transcendently expressed that we do not own material possessions. This sentence reminds us that there are fundamental philosophical questions about the nature of material ownership (Pendlebury et al, 2001;Uyl & Rasmussen, 2003;Taylor, 2005;Curchin, 2007;Brian, 2010;Ypi, 2011). Consider the following scenario.…”
Section: Themesmentioning
confidence: 99%
“…Forty years ago, John Lennon sang, "Imagine no possessions, I wonder if you can". The concept of possession itself is interesting to consider, and investigate, and debate (Curchin, 2007). A recent report explained happiness and well-being as agential flourishing (Raibley, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that some recent philosophical studies have argued that there is no self-ownership of one's own body, to say nothing of material ownership (Pendlebury et al, 2001;Uyl & Rasmussen, 2003;Taylor, 2005;Curchin, 2007;Ypi, 2011), and that further research is necessary to more fully address the distinction of self-ownership and no ownership, both psychologically and philosophically.…”
Section: Directions For Future Researchmentioning
confidence: 99%